Internalisasi Karakter Peduli Lingkungan Melalui Program Adiwiyata: Studi Kasus Praktik Baik di SMP Negeri 22 Semarang - Agnisa Martin Safa’ati; Tutik Wijayanti (Journal of Education, Humaniora and Social Sciences (JEHSS), 2026)
This article aims to examine the internalization of environmental care character through the implementation of the Adiwiyata School Program in shaping students’ environmental care character at SMP Negeri 22 Semarang. The problem is focused on how the program is implemented to foster students’ attitudes, behaviors, and awareness toward environmental sustainability within the school context. To approach this issue, theories of character education and environmental education are used as the conceptual framework. Data were collected through observation, interviews, and documentation, and analyzed qualitatively using a descriptive approach involving data reduction, data display, and conclusion drawing. The findings indicate that the implementation of the Adiwiyata School Program has been carried out systematically and integrated into school policies, curriculum, habituation activities, and the provision of environmentally friendly facilities. The program has a positive impact on the development of students’ environmental care character, as reflected in increased discipline, responsibility, creativity, and concern for cleanliness and environmental preservation. This study concludes that the Adiwiyata School Program plays a strategic role in fostering a sustainable culture of environmental awareness and creating a healthy, comfortable, and educational learning environment for the entire school community. Academically, this study contributes to the discourse on environment-based character education by explaining how policy integration, habituation, and role modeling function as key mechanisms in sustaining an environmental care culture at school.